DEPRESSION IN MYOCARDIAL INFARCTION PATIENTS AT AYUB TEACHING HOSPITAL ABBOTTABAD - Maqsood, Saeed; Jehangiri, Attiq ur Rehman; Khan, Muhammad Nadeem; Hayat, Umar; Ajmal, Seemab; Mushtaq, Maryam; Khan, Muhammad Naseem; Shah, Syed Fahad; Khan, Hamid Nisar (Journal of Ayub Medical College Abbottabad, 2017)
Background: There is a considerably high prevalence of depression in post myocardial infarction (MI) patients. This study was designed with an aim to detect depression in patients with acute MI admitted to the CCU at Ayub Teaching Hospital Abbottabad. Methods: This descriptive cross-sectional study enrolled 246 male and female patients with acute MI. The patients were interviewed on the 3rd day of admission and their answers were marked according to the HADS-D scale. Results: With a cut-off score of 11, the frequency of depression in study participants was 27.24% (n=67). No statistically significant association was found between the age and sex of patients and depression. Conclusion: Depression is fairly common following acute MI and the management plans should include a consultation with psychiatric for individualized management of depression in post myocardial infarction patients. Keywords: Depression; Anxiety; Myocardial Infarction; Stress; Quality of Life